The By-Line awards : talks presented at the ceremonies honoring Marquette University journalism alumni - Bovée, Warren G., 1922- (Marquette University Press, 1995)
A collection of edited talks presented at the Marquette University By- Line Award ceremonies from 1946 to 1994, plus biographies of all of the recipients of the award. Topics of speeches include Catholic education's negative attitude toward the journalism profession, newspaper marketing, the Pulitzer Prize, Black journalists, and journalists in the information age. No index. Annotation copyright by Book News, Inc., Portland, OR.